Preliminary Results of a Combined Score Based on sIL2-Rα and TIM-3 Levels Assayed Early After Hematopoietic Transplantation - Leotta, Salvatore; Sapienza, Giuseppe; Camuglia, Maria Grazia; Avola, Giuseppe; Marco, Annalia Di; Moschetti, Gaetano; Curto Pelle, Angelo; Markovic, Uros; Milone, Giulio Antonio; Cupri, Alessandra; Bianco, Oriana; Frontini, Viviana; et al. (Frontiers in Immunology, 2020)
Assays of cytokines in the plasma at the onset of graft-vs. -host disease (GVHD) can predict disease severity and treatment-related mortality (TRM); however, the optimal time during which cytokines should be tested and the specific panel of cytokines with the highest predictive ability remain unknown. We chose a predefined time point, 18 days after hematopoietic stem cell transplantation (HSCT), to measure the levels of six cytokines in the plasma: soluble interleukin-2 receptor alpha (sIL2-Rα), T-cell immunoglobulin domain and mucin domain-3 (TIM-3), suppression of tumorigenicity-2 (ST-2), intercellular adhesion molecule (ICAM-1), interferon-gamma (IFN-γ), and interleukin-6 (IL-6). The study included 95 patients, who underwent allogeneic hematopoietic transplantation at our institution. Plasma levels of sIL2-Rα and TIM-3, measured as continuous data, had predictive value for overall survival (sIL2-Rα, p = 0.002; TIM-3, p = 0.0007), while TRM could be predicted by sIL2-Rα (p = 0.0005), IFN-gamma (p = 0.01), and IL-6 (p = 0.0001). No cytokine was associated with the risk of relapse. Patients were categorized into groups, according to cytokine thresholds determined by receiver operating characteristic curve analysis (sIL2-Rα ≤ or > 8,100 pg/ml; TIM-3 ≤ or > 950 pg/ml) and multivariate analysis was conducted. High levels of both TIM-3 and sIL2-Rα were significant predictors of poor survival [TIM-3 > 950 pg/ml: hazard ratio (HR) = 6.214 (95% CI 1.939–19.910), p = 0.002 and sIL2-Rα > 8.100 pg/ml: HR = 2.644 (95% CI 1.308–5.347), p = 0.006]. Using these cutoff thresholds, we constructed a composite scoring system that could distinguish three different groups of patients with varying rates of TRM: high risk, 41.7%; intermediate risk, 10.8%; and low risk, 7.1% (Gray's test: p = 0.001). If confirmed in a validation cohort, this composite scoring system could be used to guide the modulation of post-transplant immune suppressive therapy.